110th Anniversary: A Case Study on Developing Accurate and Reliable Excess Gibbs Energy Correlations for Industrial Application - Mathias, Paul M (Industrial & engineering chemistry research, 2019)
Excess Gibbs energy (G E) or activity-coefficient models have a strong niche in applied thermodynamics since they provide an effective method to correlate and estimate phase equilibrium for nonideal systems. The history of their development is well represented by many papers in the technical literature, and notably in the five score and ten years of publications in Industrial & Engineering Chemistry. The science and technology has moved from formulating and establishing ideas and concepts to the automation of modern software, where phase-equilibrium correlations are often developed by algorithms with little or no expert human intervention. In addition, there is belief among practitioners that increasingly theoretical models, based upon molecular thermodynamics, will lead to more accurate correlations and with wider applicability. In this paper we use an apparently complex, but actually simple system (the lower alcohols), to study the development of G E correlations for industrial application. The subjects focused on are (1) use of multiproperty data, (2) property trends within the family of compounds, and (3) the need for advanced models.